Pedagogical Services of Christian Religious Extension Workers: Efforts to Realize Educative Functions in the Middle of Community - Imeldawati, Tiur; Hutagalung, Tasya Ivana; Natalia, Putri (LPPM IAKN Tarutung, 2023)
This research was conducted after observing current families who are facing many challenges and threats from various things that threaten family resilience. There is a negative trend that becomes the umrah hall in society where the family experiences separation, chaos, deviation, and damage so that they are no longer able to contribute positively to society. Families need strengthening, especially through Christian religious education. Therefore, the purpose of this paper is to analyze extension services through pedagogical services provided to the target community. This paper is a study of various matters related to the role of pedagogical services provided by extension workers in relation to family resilience by strengthening family spirituality through messages and narratives in the Bible; carry out the development of relations between families and wider social units; accompanying parents to take responsibility for their children's education from an early age